The The Effect of Inflation and Investment Growth Rate on Local Income in South Sumatra 2018-2020 - Hartati, Sukmini (Jurnal Ekonomi Kuantitatif Terapan, 2023)
According to the national development mission, which calls for the realization of an independent, prosperous, and united society based on Pancasila and the 1945 Constitution. One of the strategies for improving the nation's standard of living is economic growth, involving local governments' use of natural resources and initiatives to increase products per capita. This study examines how regional original income in the Regencies/Cities of South Sumatra Province is affected by investment growth and inflation between 2018 and 2020, partially and simultaneously. The analysis in this study is done with panel data, which is a combination of cross-sectional and time-series data. Locally generate revenue is negatively impacted by the inflation rate, as this study demonstrates. Meanwhile, the rate of investment growth has a positive impact on local revenue. Local revenue is positively impacted by both inflation and the investment growth rate simultaneously.